(untitled) (Transport systems and technologies, 2018)
The article discusses the installation of electrical discharge machining which is designed to recover the necks of wheelset axles electro method. Details described EDM technology, which is based on polar material transfer from the electrode to the workpiece during the electrical discharge pulse therebetween. Research surface after recovery showed that the hardness of the coating is greater than the hardness of the base and the coating bond strength with the basis of appropriate strength very foundation. Metallography revealed the presence of a small number of pores which make no significant effect on the wear resistance of the coating and the further surface of the plastic deformation amount is reduced to zero. Electric Discharge cover for its mechanical properties virtually no different from the properties of the metal parts. Using the EDM method prolonging the axis of the service, allows treatment without special surface preparation that special conditions robots ruled the thermal effect on the geometric dimensions of its parts and physics – mechanical properties, allows to obtain the coating thickness of more than five mm and a hardness of 62 HRC Recovered axes permitted for use in accordance with applicable regulations.